Anggaran Pendapatan dan Belanja Daerah di Era Desentralisasi - Agusniar Rizka Luthfia (Journal of Business Inflation Management and Accounting, 2026)
In the era of fiscal decentralization, the City of Surakarta has shown rapid development and is often seen as investment-friendly. A key indicator of local government performance is the growth of the Regional Revenue and Expenditure Budget (APBD), which increased markedly between 2006 and 2015. However, nominal APBD growth does not necessarily indicate fiscal health or alignment with public interests. This study analyzes the structure and composition of Surakarta’s APBD to assess fiscal independence and expenditure orientation. Findings show that Local Own-Source Revenue (PAD) contribution remains low, with heavy reliance on central government transfers. This indicates that APBD structure and spending are not fully aligned with public needs. Strengthening PAD and improving expenditure quality are recommended to achieve a healthier, more independent, and welfare-oriented regional budget.